Against all odds - Soni, Shriprakash; Saxena, Rohini Sawalkar (International research journal of management, IT and social sciences, 2017)
A successful woman entrepreneur, Ms. Vrinda Navare has established ‘Vrinda’s Bakes & Fast Food’ in 1993 initially with manufacturing of bakery products only. Later on in the year 1996, fast food items were added in product basket as a need of the hour. At present, the firm’s turnover is Rs. 90 lakhs with 15 full-time and 30 part-time workers. Currently the firm has 75+ products. Several types of bakery products, several varieties of snacks ranging from Rs. 5 to Rs. 25 categories and value for money mini lunches in the range Rs.15 to Rs. 30. Now the firm has also started a special unit of ‘Beverage Products’ with substantial footfall in its initial stage. Present case deals with the Entrepreneurial and Startup Challenges and strategic solutions.